2018
DOI: 10.3389/fneur.2018.00317
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Effective Connectivity of the Right Anterior Insula in Primary Insomnia

Abstract: ObjectiveDaytime cognitive impairment is an essential symptom of primary insomnia (PI). However, the underlying neural substrate remains largely unknown. Many studies have shown that the right anterior insula (rAI) as a key node of salience network (SN) plays a critical role in switching between the executive control network (ECN) and the default mode network (DMN) for better performance of cognitively demanding tasks. Aberrant effective connectivity (directional functional connectivity) of rAI with ECN or DMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…In terms of the association among these networks, the key switching role of SN in the modulation of DMN and ECN has been well-documented ( 17 , 19 21 ). The right anterior insula in SN plays a key role in modulating ECN and DMN for better task performance ( 51 ). An intact SN drives DMN and ECN during resting and task states, respectively, and contributes to maintaining normal cognitive function in healthy young ( 52 ) and old ( 21 ) subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the association among these networks, the key switching role of SN in the modulation of DMN and ECN has been well-documented ( 17 , 19 21 ). The right anterior insula in SN plays a key role in modulating ECN and DMN for better task performance ( 51 ). An intact SN drives DMN and ECN during resting and task states, respectively, and contributes to maintaining normal cognitive function in healthy young ( 52 ) and old ( 21 ) subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the AIC BOLD and EEG gamma frequency power was also greater reflecting negative affect in PI (12). While, the effective connectivity of the AIC was found decreased in PI (45). Combing with these evidences, the increased variance of dALFF might reflect overactive but ineffective activity of the AIC in PI.…”
Section: Discussionmentioning
confidence: 76%
“…Some of the differences between our results and the other studies were in part due to focusing on different structures, since we only targeted the thalamus, prefrontal cortex, parietal lobe, brain stem, vermis and cerebellar hemispheres, sensorimotor region, auditory cortex, amygdala, and caudate nucleus. These regions have been observed to be affected in patients with insomnia, in addition to several other structures such as the insula or middle frontal gyrus [26,28,45].…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Other fMRI studies comparing functional connectivity in insomnia patients to that in controls revealed an association with the insular cortex, middle frontal gyrus, prefrontal cortex, parietal lobe (particularly the precuneus), and head of the caudate nucleus [26,27]. Additionally, functional connectivity between the cerebellum and various cortical structures is altered in patients with insomnia [28].…”
Section: Introductionmentioning
confidence: 98%